Enhancing Employee Engagement through Strategic Human Resource Management in Economics and Management Education - Herawaty, Mety Titin; Mutia, Fara; Asmadi, Iwan; Gampu, Seska; Aprillia, Aprillia (Jurnal Sains Sosio Humaniora, 2025)
This study explores how SHRM enhances employee engagement in higher education, particularly within economics and management education. Using a qualitative library research design and thematic content analysis, the study reviewed scholarly sources published between 2014 and 2024. Literature selection followed explicit inclusion–exclusion criteria, incorporating academic works addressing SHRM, employee engagement, leadership, organizational culture, or HRM in higher education, while excluding non-scholarly publications and studies lacking methodological clarity. The findings show that SHRM strengthens engagement when aligned with institutional strategy, supported by transformational leadership, and embedded within a participatory organizational culture. Four clusters of HR practices competency-based planning, continuous professional development, performance-based rewards, and participatory performance management emerge as key drivers of engagement through their effects on motivation and organizational commitment. Based on these insights, the study proposes a conceptual model explaining how SHRM enhances cognitive, emotional, and behavioral engagement, ultimately improving teaching performance, research productivity, and institutional competitiveness. The results contribute to the limited academic literature on SHRM in higher education and offer practical guidance for universities seeking to build integrated HR strategies. Future empirical research is recommended to validate the proposed model across diverse academic contexts.